2006
DOI: 10.1111/j.1462-5822.2005.00619.x
|View full text |Cite
|
Sign up to set email alerts
|

Cryptococcus neoformans capsular polysaccharide component galactoxylomannan induces apoptosis of human T-cells through activation of caspase-8

Abstract: SummaryThe major virulence factor of Cryptococcus neoformans is its polysaccharide capsule composed of glucuronoxylomannan (GXM), galactoxylomannan (GalXM) and mannoproteins. A variety of immunomodulating activities have been described for GXM and mannoproteins but little is known about possible interactions of GalXM with the immune system. In the present article, we investigate the effect of purified soluble GalXM on human T lymphocytes. The results indicate that, GalXM (i) can affect selected immune response… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
68
1
1

Year Published

2008
2008
2022
2022

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 68 publications
(73 citation statements)
references
References 35 publications
3
68
1
1
Order By: Relevance
“…It has been shown that some bacterial capsular polysaccharides, such as the Cryptococcus neoformans, glucuronoxylomannan (GXM), induce the upregulation of CD95L on the macrophages and, as a consequence, apoptosis of the lymphocytes (14,21,22). This same phenomenon is reported in human protozoan parasite Trypanosoma cruzi (T. cruzi) (23).…”
Section: Introductionsupporting
confidence: 49%
“…It has been shown that some bacterial capsular polysaccharides, such as the Cryptococcus neoformans, glucuronoxylomannan (GXM), induce the upregulation of CD95L on the macrophages and, as a consequence, apoptosis of the lymphocytes (14,21,22). This same phenomenon is reported in human protozoan parasite Trypanosoma cruzi (T. cruzi) (23).…”
Section: Introductionsupporting
confidence: 49%
“…The relatively small amount of GalXM in the four samples indicates that the contribution of this PS to the average measurements presented in this study is small, with the caveat that it may contribute to differences in apparent molecular mass if, indeed, it promotes PS aggregation. However, these results also indicate that assigning specific biological functions to PS preparations should be done cautiously, since GalXM is a powerful immunomodulator (18) and even small amounts of GalXM in PS preparations may produce confounding results. Even considering the presence of GalXM in the PS fractions, the percent composition of each sugar differed between samples.…”
Section: Discussionmentioning
confidence: 85%
“…Xylose units can be associated to branched mannose through ␤(1,3) or ␤(1,2) linkages (22). GalXM has an average mass of 100 kDa and has potent deleterious effects on immunological function (11,12,18). GXM is a high-molecular-mass PS with a complex structure.…”
mentioning
confidence: 99%
“…Minor capsular components include galactoxylomannan (GalXM) and mannoprotein 1 (MP1). The capsule is a key virulence factor, with myriad roles including antiphagocytic activities (29) and immunomodulatory functions during adaptive immune responses (15,46,61). Interestingly, the capsule has also been shown previously to be important for dissemination from the lungs (9), and the capsular component GalXM has been shown to facilitate dissemination to the central nervous system (44).…”
mentioning
confidence: 99%